Institutional investment patterns and corporate financial behavior in the United States and Japan - Prowse, Stephen D. (Journal of Financial Economics, 1990)
This paper examines the agency problem between shareholders and debtholders of Japanese and U.S. firms. Whereas U.S. institutional investors are restricted from doing so, Japanese financial institutions take large equity positions in firms to which they lend, particularly in firms more susceptible to the agency problem. Debt ratios of U.S. firms are negatively related to the firm's potential to engage in risky, suboptimal investments, whereas Japanese debt ratios show no such relation. The evidence is consistent with the notion that the agency problem is mitigated to a greater degree in Japan than in the U.S.